An overview of systematic reviews of normal labor and delivery management - Mina Iravani; Mohsen Janghorbani; Elahe Zarean; Masoud Bahrami (Wolters Kluwer Medknow Publications, 2015)
Background: Despite the scientific and medical advances for management of complicated health issues, the current maternity care setting has increased risks for healthy women and their babies. The aim of this study was to conduct an overview of published systematic reviews on the interventions used most commonly for management of normal labor and delivery in the first stage of labor. Materials and Methods: The online databases through March 2013, limited to systematic reviews of clinical trials were searched. An updated search was performed in April 2014. Two reviewers independently assessed data inclusion, extraction, and quality of methodology. Results: Twenty-three reviews (16 Cochrane, 7 non-Cochrane), relating to the most common care practices for management of normal labor and delivery in the first stage of labor, were included. Evidence does not support routine enemas, routine perineal shaving, continuous electronic fetal heart rate monitoring, routine early amniotomy, and restriction of fluids and food during labor. Evidence supports continuity of midwifery care and support, encouragement to non-supine position, and freedom in movement throughout labor. There is insufficient evidence to support routine administration of intravenous fluids and antispasmodics during labor. More evidence is needed regarding delayed admission until active labor and use of partograph. Conclusions: Evidence-based maternity care emphasizes on the practices that increase safety for mother and baby. If policymakers and healthcare providers wish to promote obstetric care quality successfully, it is important that they implement evidence-based clinical practices in routine midwifery care.